Money and banking in Japan (Tokyo : Bank of Japan, Economic Research Dept., 1964)
"Money and Banking in Japan" reviews the historical development of money and banking, the functioning of the nation's monetary structure, and the present state of financial institutions. This brochure seeks to clarify as much as possible the special characteristics of Japan's money and banking, thus to provide a better understanding of its system and functions.
rpm 26/04/2018
Ref
Keywords: Money; Banks and banking; Financial institutions; Japan